1982
DOI: 10.1037/0096-1523.8.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Bright sneezes and dark coughs, loud sunlight and soft moonlight.

Abstract: Synesthetic metaphors (such as "the dawn comes up like thunder") are expressions in which words or phrases describing experiences proper to one sense modality transfer their meanings to another modality. In a series of four experiments, subjects used scales of loudness, pitch, and brightness to evaluate the meanings of a variety of synesthetic (auditory-visual) metaphors. Loudness and pitch expressed themselves metaphorically as greater brightness; in turn, brightness expressed itself as greater loudness and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
4

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 9 publications
4
62
0
4
Order By: Relevance
“…Similarly, when Marks (1974) and Smith and Sera asked people to match sounds varying in loudness to contrasting levels of surface brightness, the same inconsistency was apparent, with some people aligning lighter with louder (more than), and others aligning it with quieter (less than). And, with a different task situation, Marks (1982) confirmed that whereas illuminant brightness aligns itself consistently with loudness as a magnitude dimension, surface brightness does not. When he created metaphorical verbal expressions combining visual and auditory terms, he found that although words referring to contrasting levels of illuminant brightness (e.g., dim and bright) consistently altered the imagined loudness of a named sound with which it was combined (e.g., dim sound of violin), words referring to different levels of surface brightness (e.g., dark, gray, and black) did not (e.g.…”
Section: Appendixsupporting
confidence: 54%
See 2 more Smart Citations
“…Similarly, when Marks (1974) and Smith and Sera asked people to match sounds varying in loudness to contrasting levels of surface brightness, the same inconsistency was apparent, with some people aligning lighter with louder (more than), and others aligning it with quieter (less than). And, with a different task situation, Marks (1982) confirmed that whereas illuminant brightness aligns itself consistently with loudness as a magnitude dimension, surface brightness does not. When he created metaphorical verbal expressions combining visual and auditory terms, he found that although words referring to contrasting levels of illuminant brightness (e.g., dim and bright) consistently altered the imagined loudness of a named sound with which it was combined (e.g., dim sound of violin), words referring to different levels of surface brightness (e.g., dark, gray, and black) did not (e.g.…”
Section: Appendixsupporting
confidence: 54%
“…If surface brightness is not distinct from illuminant brightness and, like the latter, behaves as a magnitude dimension, then the nature of the predicted correspondence would contradict a structural account, because on a structural account, smaller (less size) should be aligned with darker (less light), rather than with brighter (more light). Of course, if surface brightness is distinct from illuminant brightness and does not behave as a magnitude dimension, as the evidence suggests (see, e.g., Marks, 1974Marks, , 1982Marks, , 1987Smith & Sera, 1992;Wicker, 1968; see the Appendix for an account of the evidence), then this in itself precludes it from entering into a correspondence with a structural basis.With regard to the predicted size-brightness correspondence having either a statistical or a linguistic basis, there is little evidence to support either possibility. Although it is acknowledged that without a comprehensive analysis of either the natural world of objects, or of the language of cross-sensory correspondences, it is difficult to make claims with any confidence, it has been claimed that there are no natural co-occurrences from which the correspondence could be derived (Mondloch & Maurer, 2004;Smith & Sera, 1992), and it is difficult to find any words in common use (at least in English) that mark contrasting values on both dimensions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although illuminant brightness can function as a magnitude dimension (see, e.g., Marks, 1987), pitch and surface brightness appear not to (see, e.g., Marks, 1974Marks, , 1982Marks, , 1987Smith & Sera, 1992), and so correspondences involving them are unlikely to have a structural basis. Because it is unclear whether angularity and hardness also can function as magnitude dimensions, it remains uncertain whether they can enter into correspondences having a structural basis.…”
Section: Discussionmentioning
confidence: 99%
“…Marks, 1987, for evidence that these are distinct types of brightness and that it is the latter that is being manipulated in Experiment 4). 18 Unlike perceived illuminant brightness, perceived surface brightness is not a magnitude dimension (not prothetic in Stevens's, 1957, terminology) (see Marks, 1974Marks, , 1982Marks, , 1987Smith & Sera, 1992). Because of this, these two types of brightness can show different patterns of correspondence (e.g., both forms of brightness interact with auditory pitch to give rise to congruity effects in speeded classification, but only perceived illuminant brightness interacts with loudness to yield such effects; see Marks, 1987).…”
Section: Experiments 4: Visual Angularity and Brightness Conveyed Visumentioning
confidence: 99%